A Rare Manifestation of a Rare Disease: Mantle Cell Lymphoma Presenting With Aseptic Meningitis - Elvira Umyarova MD; Sreedhar Adapa MD; Srikanth Naramala MD; Vijay Gayam MD; Narothama Reddy Aeddula MD; Venu Madhav Konala MD (SAGE Publishing, 2019)
Mantle cell lymphoma (MCL) is a rare form of non-Hodgkin lymphoma characterized by clonal proliferation of follicular mantle zone B lymphocytes. It is caused by abnormal chromosomal translocation t(11;14) resulting in aberrant expression of cyclin D1. This leads to activation of anti-apoptotic pathways and abnormal proliferation of MCL cells. Patients can present with an indolent course or a fulminant disease with short overall survival. The disease frequently involves extranodal organs, but rarely manifests with neurological symptoms. We report a rare case of aberrant CD5-negative MCL presenting with aseptic meningitis.